The critical phonon scattering and peculiarities of the transport phenomena in ferroelectric crystal - Altukhov, V.I.; Strukov, B.A. (Condensed Matter Physics, 2002)
The review of the theoretical study of the critical phonon scattering and anomalous heat transport near the phase transition temperature Tc is presented. An interpretation and quantitative approach to the description of the anomalous temperature dependence of the thermal conductivity λ(T) near Tc are discussed. Представлено огляд теоретичних досліджень критичного розсіяння фононів і аномального переносу тепла поблизу температури фазового переходу Tc. Обговорюється інтерпретація і кількісний підхід до опису аномальної температурної залежності A(T) поблизу Tc.